Experimental research on damage characteristics of multi-spaced plates with long rods of steel and W-Zr reactive material at hypervelocity impact. (April 2022) - Shang, Cheng; Ren, Tianfei; Zhang, Qingming; Lu, Yangyu; Long, Renrong; Guo, Xianghua; Hu, Xin
Graphical abstract: Highlights: Dynamic compression characteristics and reaction behavior of W-Zr reactive material are investigated. Hypervelocity impact experiments of long rods on multi-spaced plates are performed. The debris clouds during the impact process are recorded with a high-speed camera. Damage properties of the multi-spaced plates with long rods are obtained and compared. W-Zr reactive material has the damage effects of kinetic and chemical energy. Abstract: The damage or penetration research of the long rods has attracted more and more attention from scholars worldwide. In this article, the dynamic compression tests of W-Zr reactive material are performed. Six experiments of the long rods impacting the multi-spaced plates at hypervelocity are carried out on a two-stage light gas gun. Two kinds of long rods, inert 40CrNi2MoA steel and W-Zr reactive material, are used. The initial impact speed ranges from 2040 m/s to 3200 m/s. According to results, W-Zr reactive material reacts at the strain rate of 2200 s −1 and higher, whose strength limit is related to the strain rate. The long rods can produce debris clouds when hitting the multi-spaced plates at the speed of 2040 m/s and higher, causing large perforation and great damaged area in the subsequent plates. The perforations and damaged areas of the multi-spaced plates depend on the specific kinetic energy of the long rods. The violent reaction behavior of the W-Zr reactive material helps to cause large perforation and damaged area of the subsequent plates than inert materials. It proves that the damage ability of the W-Zr reactive material is stronger than that of the inert material with a similar density.